Defining the seasonality of respiratory syncytial virus around the world: National and subnational surveillance data from 12 countries. Issue 6 (13th July 2021) - Staadegaard, Lisa; Caini, Saverio; Wangchuk, Sonam; Thapa, Binay; de Almeida, Walquiria Aparecida Ferreira; de Carvalho, Felipe Cotrim; Fasce, Rodrigo A.; Bustos, Patricia; Kyncl, Jan; Novakova, Ludmila; Caicedo, Alfredo Bruno; de Mora Coloma, Domenica Joseth; et al.
Abstract : Background: Respiratory syncytial virus (RSV) infections are one of the leading causes of lower respiratory tract infections and have a major burden on society. For prevention and control to be deployed effectively, an improved understanding of the seasonality of RSV is necessary. Objectives: The main objective of this study was to contribute to a better understanding of RSV seasonality by examining the GERi multi‐country surveillance dataset. Methods: RSV seasons were included in the analysis if they contained ≥100 cases. Seasonality was determined using the "average annual percentage" method. Analyses were performed at a subnational level for the United States and Brazil. Results: We included 601 425 RSV cases from 12 countries. Most temperate countries experienced RSV epidemics in the winter, with a median duration of 10–21 weeks. Not all epidemics fit this pattern in a consistent manner, with some occurring later or in an irregular manner. More variation in timing was observed in (sub)tropical countries, and we found substantial differences in seasonality at a subnational level. No association was found between the timing of the epidemic and the dominant RSV subtype. Conclusions: Our findings suggest that geographical location or climatic characteristics cannot be used as a definitive predictor for the timing of RSV epidemics and highlight the need for (sub)national data collection and analysis.